Water-ethanol blending effects on combustion performance of methane-air premixed-flame burners. (1st September 2022) - Yang, Hui Man; Yeo, Ji Hun; Kim, Nam Il
Graphical abstract: Highlights: Water and ethanol vapors were supplied to a methane-air premixed-flat-flame burner. Flame stabilization of ceramic-honeycomb and metal-fiber burners were studied. Simulated CO/NO emissions were compared and radiative heat transfer was examined. Lifecycle CO2 and NOx could be reduced with sufficient stability and efficiency. Abstract: Recently, water injection into the recuperator of a condensing boiler was employed to achieve higher thermal efficiency and lower NOx emission simultaneously. In addition, biofuel blending was adopted to reduce the lifecycle CO2 emission. In this study, injection of a water-biofuel mixture into a condensing boiler was proposed to provide both advantages simultaneously. Ethanol was selected as the surrogate of a water-miscible biofuel. As an essential step in its technical realization, the combustion performances of methane-air premixed-flame burners were examined with variations in the concentrations of methane, ethanol, and water. Flame stabilization characteristics were examined for two kinds of burners: a ceramic-honeycomb burner and a metal-fiber burner. The effects of water and ethanol blending on CO and NO emissions were examined. The product gas had an orangish light, and its emission spectra and emissive power were investigated. Conclusively, it was shown that blending water with a miscible biofuel (or ethanol) could reduce the lifecycle CO2 emission and achieve the better combustion performances required for commercial premixed-flame burners of condensing boilers. A mixture of the same water and ethanol vapor volume could reduce NO by 70%, and ethanol blending with methane could increase radiative heat transfer from the product gas by approximately 20%.